Beyond Organoleptic Characteristics: The Pharmacological Potential of Flavonoids and their Role in Leukocyte Migration and in L‐Selectin and β2‐Integrin Expression During Inflammation. (12th March 2014) - Suyenaga, Edna Sayuri; Klein‐Júnior, Luiz Carlos; Passos, Carolina dos Santos; Marin, Rafaela; Santin, José Roberto; Machado, Isabel Daufenback; Farsky, Sandra Helena Poliselli; Henriques, Amélia Teresinha
<x xml:space="preserve">Abstract</x> Flavonoids are compounds responsible for several organoleptic characteristics of plant‐derived foods. They are also bioactive compounds with antiinflammatory role. Different mechanisms for this activity have been reported, but their effects on cell migration are not fully understood. In the present study, the role of flavonoids on leukocyte migration in vivo was investigated, using the carrageenan‐induced pleurisy model and intravital microscopy in rats. It was found that quercetin (1), rutin (2), flavone (5), apigenin (6) and flavonol (7) reduced cell migration to the pleural cavity and inhibited rolling, adhesion and transmigration. Additionally, flow cytometry assays showed that the in vitro treatment with all compounds (15–60 µm) did not cause cell death and 1 inhibited the cleavage of L‐selectin and the β2‐integrin expression, whereas 2 and 7 only inhibited the β2‐integrin expression. Together, data herein presented clearly show the ability of flavonoids to inhibit in vivo neutrophil influx into inflamed tissue, by acting in different mechanisms of neutrophil migration. Copyright © 2014 John Wiley & Sons, Ltd.